(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to identify the role of performance auditing on enhancing the banking marketing, diagnosing the extent of his contribution to strengthening it, improving its effectiveness, and increasing its efficiency in the studied banks, and identifying the necessary indicators to be adopted to audit banking marketing performance and its dimensions (Product, price, promotion, Place, People, physical evidence, Process) in the studied banks. The problem of the research was defining by the main question (Are there an effect for performance auditing in enhancing the banking marketing?). The research was applied in Al-Rafidain and Al-Rasheed Banks using performance audit indicators which prepared by the Federal Board of Supreme Audit, The research adopted the descriptive analytical method in its theoretical and practical aspects. The research reached to many of results the most important of it are the following: • There is a significant role for the performance audit on improving the banking marketing in Al-Rafidain and Al-Rasheed Banks. There are many performance audit indicators prepared by the Federal Office of Financial Supervision that can be used to audit the performance of banking marketing, but they need to be updated and developed in order to include all aspects of banking marketing